The housemaid [videorecording (DVD)] - Nguyen, Derek; Nguyen, Derek; Nhung, Kate; Richaud, Jean-Michel; Kovalenko, Svitlana (Shout! Factory, 2018)
An orphan Vietnamese girl who works as a housemaid at a French rubber plantation falls in love with the landowner but their romance angers the ghost of his dead wife.